Graphic novels in your school library - Karp, Jesse; Kress, Rush (American Library Association, 2012)
To dismiss the educational potential of the graphic novel is to throw away a golden opportunity to reach out to young readers. Learn how the format has become entwined in our culture, and the ways graphic novels can be used in the library and in the classroom